Subarachnoid hemorrhage : incidence, risk factors and sex differences - Lindekleiv, Haakon (University of Tromsø, 2011)
The papers of this thesis are not available in Munin: 1.Lindekleiv H, Njølstad I, Ingebrigtsen T and Mathiesen EB.: 'Incidence of aneurysmal subarachnoid hemorrhage in Norway 1999-2007', Acta Neurologica Scandinavia (2011) 123(1):34-4. Available at http://dx.doi.org/10.1111/j.1600-0404.2010.01336.x 2. Sandvei MS, Lindekleiv H, Romundstad PR, Müller T, Vatten L, Ingebrigtsen T, Njølstad I, Mathiesen E and Vik A.: 'Risk factors for aneurysmal subarachnoid hemorrhage - BMI and serum lipids: 11-years follow-up of the HUNT and the Tromsø Study in Norway', (accepted paper in Acta Neurologica Scandinavia). 3. Lindekleiv H, Sandvei MS, Njølstad I, Løchen M-L, Romundstad PR, Vatten L, Ingebrigtsen T, Vik A and Mathiesen EB.: 'Sex differences in risk factors for aneurysmal subarachnoid hemorrhage. The HUNT and Tromsø studies', Neurology (2011) vol.76(7):637-43. Available at http://dx.doi.org/10.1212/WNL.0b013e31820c30d3 4. Lindekleiv HM, Valen-Sendstad K, Mardal K-A, Morgan M, Faulder K, Magnus JH, Romner B and Ingebrigtsen T.: 'Sex differences in intracranial arterial bifurcations', Gender Medicine (2010) vol. 7(2):149-55. Available at http://dx.doi.org/10.1016/j.genm.2010.03.003 Subarachnoid hemorrhage (SAH) is bleeding into the subarachnoid space surrounding the brain. SAH may occur spontaneously, or following traumatic brain injury. Spontaneous SAH is in 85% of cases caused by rupture of an outpouching (aneurysm) of an intracranial artery. This is called an aneurysmal SAH (aSAH). The main findings of the present thesis concerned the incidence of aSAH in Norway, and sex differences in the risk factors for aSAH. The data source was the Norwegian Patient Register, and a combined cohort of the Tromsø study and the Nord-Trøndelag Health Study. The crude incidence of aSAH in Norway decreased from 11.1 per 100,000 person-years (95% confidence interval, CI: 10.5–11.6) in the period 1999–2001 to 8.9 per 100,000 person-years (95% CI: 8.4–9.4) in the period 2005–2007. Significant regional variations were observed, indicating ...